Islamic human development index berbasis maqāṣid syarī’ah dan determinan ekonomi di negara-negara muslim - Syahruddin Kadir; Murtiadi Awaluddin; Alim Syariati (Journal of Economics Research and Policy Studies, 2026)
The Human Development Index developed by the UNDP is considered insufficient for measuring development in Muslim countries because it does not incorporate an Islamic perspective, particularly the dimensions of religion and socio-economic ethics. Therefore, this study uses the Islamic Human Development Index (I-HDI) as a more comprehensive alternative measure of human development, which is derived from the five dimensions of maqāṣid syarī’ah, namely religion (dīn), life (nafs), reason (‘aql), offspring (nasl), and wealth (māl). This study aims to analyze the effects of foreign direct investment, remittances, and unemployment on the I-HDI in Muslim countries, and to examine the moderating role of political stability. The methods used are multiple linear regression with the Generalized Method of Moments (GMM) and Moderated Regression Analysis (MRA) approaches. The results show that foreign direct investment and remittances have a significant positive effect on Islamic human development, while unemployment has a significant negative effect. In addition, political stability is a clear moderator that can strengthen the relationship between economic determinants and the Islamic Human Development Index in Muslim countries.